2012
DOI: 10.1111/j.1540-8183.2011.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Quantification of Residual Shunt after Percutaneous Patent Foramen Ovale Closure: Correlation of Device Efficacy with Intracardiac Anatomic Measures

Abstract: In an intracardiac echocardiography-defined PFO population, characterized by severe baseline Valsalva shunt and a high incidence of persistent (rest) shunting, association of six intracardiac measurements to closure device failure by multivariate logistic regression showed that the width of the left atrial opening was a strong predictor of residual shunting. An unanticipated finding was that use of a large sizing balloon was also strongly associated with failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…However, a shunt can still be detected in 10-20% of patients within 12 months after intervention. [2][3][4][5][6][7][8][9][10][11] Subsequent instrumental examinations are limited to patients with severe, persistent RLS or cerebrovascular events, and the behavior of small residual RLSs after the first year of follow-up is largely undetermined. Moreover, the prognostic impact complete occlusion is still under debate, with evidence suggesting that complete closure may result in fewer neurological recurrences, 11,12 while a recent meta-analysis 13 reported no significant differences in terms of clinical events for patients with a persistent residual RLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a shunt can still be detected in 10-20% of patients within 12 months after intervention. [2][3][4][5][6][7][8][9][10][11] Subsequent instrumental examinations are limited to patients with severe, persistent RLS or cerebrovascular events, and the behavior of small residual RLSs after the first year of follow-up is largely undetermined. Moreover, the prognostic impact complete occlusion is still under debate, with evidence suggesting that complete closure may result in fewer neurological recurrences, 11,12 while a recent meta-analysis 13 reported no significant differences in terms of clinical events for patients with a persistent residual RLS.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that after closure, the mechanical action of the prosthesis and its endothelization will finally seal the communication between the atria, thus allowing the patient to discontinue antithrombotic therapy. However, a shunt can still be detected in 10–20% of patients within 12 months after intervention . Subsequent instrumental examinations are limited to patients with severe, persistent RLS or cerebrovascular events, and the behavior of small residual RLSs after the first year of follow‐up is largely undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Diaz et al identified the shunt size at 24 hours following PFO closure as a predictor of residual shunt at follow‐up. The device size (35 mm Amplatzer PFO Occluder vs. 25 mm) was found to be associated with residual shunting by Greutman et al and Sorensen et al In our study, the amount of baseline right‐to‐left shunt, the size of closure device and the presence of residual shunt at the cavography performed immediately after the first PFO closure failed to predict residual shunting at 6 months. Although the type of device was not a predictor of residual shunting, this was nevertheless slightly, but not significantly, more frequent with the Cardia PFO Occluder.…”
Section: Discussionmentioning
confidence: 38%
“…As a consequence, we believe that type I residual shunt could be overestimated by TCD. Previous studies found that patients with an interatrial septal aneurysm undergoing PFO closure were more likely to have residual shunting at 6‐month follow‐up. In our study, more than 60% of patients with moderate‐to‐large residual shunt had an interatrial septal aneurysm, but this characteristic did not reach statistical significance as a predictor of residual shunt.…”
Section: Discussionmentioning
confidence: 93%
“…Die Kontrolle der Intervention nach Implantation eines Schirmver schlusses ist weiterhin eine Aufgabe der Ultraschallmethode. So wurde nach Behandlung eines PFO/ASA mit dem Amplatzer Oc cluder noch ein relevanter Restshunt in > 20 % der Patienten nach 3 Monaten entdeckt [25,26].…”
Section: Indikationen Für Die Rechts-links-shunt Diagnostik ▼unclassified